2012
DOI: 10.1108/15253831211217206
|View full text |Cite
|
Sign up to set email alerts
|

Regional economic integration and international strategic alliances: evidence from the EU

Abstract: Purpose -Regional economic integration has been a major area of research in the field of international economics and international trade, with little attention being paid to the impact of these economic collaborations on the organizational strategies of firms within the economically integrated regions. By building on the organization-environment relationship paradigm, this paper aims to address the impact of environmental changes associated with economic integration, market commonality and currency commonality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…First, we analyzed the number of offshoring cases and jobs restructured to identify the different offshoring phases. Second, we analyzed the annual growth rate of the global GDP (as a proxy for development opportunities and wealth of the whole economy - Alhorr et al, 2012) and the annual number of industrial robot installations (as a proxy for technological innovation diffusion in manufacturing -De Backer et al, 2018) to understand the changes in the "surrounding context" (see Table A1 in Appendix for data sources). The reasoning underpinning our approach is that firm choices are embedded in a series of contingent factors and such factors evolve over time, both in terms of changing and emerging conditions.…”
Section: Datasetmentioning
confidence: 99%
“…First, we analyzed the number of offshoring cases and jobs restructured to identify the different offshoring phases. Second, we analyzed the annual growth rate of the global GDP (as a proxy for development opportunities and wealth of the whole economy - Alhorr et al, 2012) and the annual number of industrial robot installations (as a proxy for technological innovation diffusion in manufacturing -De Backer et al, 2018) to understand the changes in the "surrounding context" (see Table A1 in Appendix for data sources). The reasoning underpinning our approach is that firm choices are embedded in a series of contingent factors and such factors evolve over time, both in terms of changing and emerging conditions.…”
Section: Datasetmentioning
confidence: 99%
“…Alhorr, Boal, and Cowden [21] found that multinational enterprises (MNEs), in the presence of regional economic integration, shift their global portfolio to a regional scope due to the perceived benefits of doing so, such as increased economies of scale and economies of scope. Additionally, the results of this research suggest that the reduction in transaction costs and regional market growth can potentially improve the performance of the MNEs [21].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Finally, the Economic and Monetary Union refers to the adoption of a single currency by all partners putting emphasis on implementation of common monetary and financial policies (Koné, 2012). Alhorr, Boal & Cowden (2012) pointed out that international trade theories argue for tariff and non-tariff barriers to protect infant industries and jobs in the domestic market. That eventually may prevent competition and raise commodity prices for the end consumers.…”
Section: Forms Of Integrationmentioning
confidence: 99%